The Effectiveness of Garlic Extract against Triglyceride Levels of Wistar Rats Induced by 50% Ethanol - Kodariah, Liah; Mendrofa, Desmawaty (Journal of Advances in Medicine and Pharmaceutical Sciences, 2022)
Alcohol affects the metabolism of triglycerides. Excessive intake of fat, carbohydrates, and protein can increase triglyceride levels. In addition to fat and carbohydrates, factors that can affect triglyceride levels are age, lifestyle, smoking, alcohol intake, hypertension, and liver disease. Triglyceride levels (> 200 mg/dL) raise the risk of atherosclerosis. The purpose of this study was to determine the levels of triglycerides of Wistar rats before and after induction of ethanol 50% and garlic extract therapy. The method was experimental, with a sample of 25 Wistar rats which were divided into 5 groups. G1, rats were given 50% ethanol from day 9-14, G2, rats were only given distilled water, G3, G4, and G5 treatment groups at doses I, II, and III, after ethanol administration 50% on the 9th – 14th day followed by the administration of garlic extract at a dose of 200 mg/gr BW, 400mg/gr BW and 600 mg/ gr BW, respectively. Rat blood was taken on the 8th day before administration of ethanol and garlic extract and taken again on the 15th day after administration of ethanol and garlic extract, then triglycerides were measured using a photometer. The results showed that there were significant differences in triglyceride levels in G1 with G2, G3, G4, and G5. Triglyceride levels in rats before treatment and after administration of 50% ethanol and garlic extract 200 mg/gramBW increased but were still within normal limits.